2015
DOI: 10.1007/s00374-015-1029-9
|View full text |Cite
|
Sign up to set email alerts
|

An in-depth analysis of actinobacterial communities shows their high diversity in grassland soils along a gradient of mixed heavy metal contamination

Abstract: Several previous studies indicated that Actinobacteria may be enriched in soils with elevated content of heavy metals. In this study, we have developed a method for the in-depth analysis of actinobacterial communities in soil through phylum-targeted high-throughput sequencing and used it to address this question and examine the community composition in grassland soils along a gradient of heavy metal contamination (Cu, Zn, Cd, Pb). The use of the 16Sact111r primer specific for Actinobacteria resulted in a datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…The higher prokaryotic diversity of the RV site agrees with the intermediate disturbance hypothesis, which indicates the capacity of environments with intermediate levels of perturbation corresponds with the highest diversity (Connell, 1978). Other studies revealed a similar pattern in that the succession process after 10 years of revegetation may favor an increase in the diversity of important ecological groups (Hong et al, 2015;Li et al, 2014), such as nitrogen-fixing bacteria (de Castro et al, 2017;Huang et al, 2011) and groups that are tolerant to metals, such as Actinobacteria (Alvarez et al, 2017;Ivshina et al, 2013;Větrovský & Baldrian, 2015). The highest diversity in RV revealed the adaptation of the prokaryotic community to environmental stress conditions.…”
Section: Discussionsupporting
confidence: 77%
“…The higher prokaryotic diversity of the RV site agrees with the intermediate disturbance hypothesis, which indicates the capacity of environments with intermediate levels of perturbation corresponds with the highest diversity (Connell, 1978). Other studies revealed a similar pattern in that the succession process after 10 years of revegetation may favor an increase in the diversity of important ecological groups (Hong et al, 2015;Li et al, 2014), such as nitrogen-fixing bacteria (de Castro et al, 2017;Huang et al, 2011) and groups that are tolerant to metals, such as Actinobacteria (Alvarez et al, 2017;Ivshina et al, 2013;Větrovský & Baldrian, 2015). The highest diversity in RV revealed the adaptation of the prokaryotic community to environmental stress conditions.…”
Section: Discussionsupporting
confidence: 77%
“…The fact that Actinobacteria appeared to increase in unison with soil nutrient contents, such as N and C content across both catenas, while relative abundances of Chloroflexi decreased, additionally points to nutrient availability driving the bacterial community structure and agrees well with the copiotrophic hypothesis (Fierer et al, 2007 ), which predicts that fast-growing soil bacteria (copiotrophs) prefer nutrient rich environments, while slower growing oligotrophs would thrive in oligotrophic soils. Many actinobacterial groups show a copiotrophic lifestyle (Leff et al, 2015 ; Chávez-Romero et al, 2016 ), and are known as heterotrophic decomposers of soil organic matter (Janssen, 2006 ; Ventura et al, 2007 ; Větrovský and Baldrian, 2015 ) or N 2 fixing bacteria (e.g., orders Frankiales and Pseudonocardiales ), which would be expected in the rhizosphere of Acacia sp. found in the catena's downslope areas but not below Combretum sp.…”
Section: Discussionmentioning
confidence: 99%
“…Dry mass content was measured as a loss of mass during freeze-drying, and the pH was measured in distilled water (1:10). The wood C and N contents were measured in an external laboratory (Research Institute for Soil and Water Conservation, Prague, Czech Republic) as described previously ( 46 ). Klason lignin content was measured as dry weight of solids after hydrolysis with 72% (wt/wt) H 2 SO 4 ( 47 ).…”
Section: Methodsmentioning
confidence: 99%